Characteristics and distribution of microplastics in surface sediment of Selat Pulau Tuba, Langkawi, Kedah / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Rusli, Hurin Haifa; Abd.Aziz, Khairul Naim; Roslani, Muhammad Akmal (Universiti Teknologi MARA, Perak, 2020)
This study aims to assess the characteristics and occurrence of the microplastics contamination in surface sediment of Selat Pulau Tuba, Langkawi, Kedah. Van Veen Grab Sampler was used to collect the samples of sediment. The samples were immediately preserved and analyzed using a Fourier-transform infrared spectrophotometer and a microscope to determine the presence and characteristics of microplastics. The result indicates the presents of polypropylene and polyethylene with a size of 500 μm -1000 μm and 1000 μm - 1500 μm respectively. Overall, Selat Pulau Tuba, Langkawi, Kedah has minimal pollution of microplastics in sediment.